Gender Inequalities in Health and Their Effect on the Economic Prosperity Represented by the GDP of Selected Developed Countries-Empirical Study - Stefko, Robert; Gavurova, Beata; Ivankova, Viera; Rigelsky, Martin (International journal of environmental research and public health, 2020)
The objective is to evaluate the relations between gender health inequalities and economic prosperity in the Organisation for Economic Co-operation and Development (OECD) countries. The groups included health indicators in the specification of men, women and gender inequalities: life expectancy, causes of mortality and avoidable mortality. The variable determining the economic prosperity was represented by the Gross Domestic Product (GDP). The analytical processing included descriptive analysis, analysis of differences and analysis of relationships. The regression analysis was presented as the main output of the research. Most of the significant gender differences in health showed a more positive outcome for women. It is possible to identify a certain relation between gender health inequalities and economic prosperity. If there is some reduction in gender inequalities in health, the economic prosperity will increase. The reduction seems to be more effective on the part of men than women. The output of the cluster analysis showed the relations of indicators evaluating the inequalities and the prosperity. The countries such as Luxembourg, Norway or Switzerland showed very positive outputs, on the other hand, the countries with a potential for the improvement are Lithuania, Latvia or Estonia. Overall, the policies should focus on reducing the inequalities in avoidable mortality as well as reducing the frequent diseases in younger people.
Keywords: Luxembourg; Female; gross domestic product; diseases; Lotyšsko; ženské pohlaví; Estonsko; Switzerland; Gross Domestic Product; Švýcarsko; lidé; prosperity of economy; Litva; life expectancy; Norway; vyspělé země; Norsko; OECD; Humans; Sex Factors; avoidable mortality; Latvia; health differences; Lucembursko; Lithuania; Male; sexuální faktory; Socioeconomic Factors; Health Status Disparities; socioekonomické faktory; hrubý domácí produkt; mužské pohlaví; mortality; gender health inequalities; disparity zdravotního stavu; health inequalities; Developed Countries; Estonia